Antiulcer Effects of Ethyl acetate Fraction of Carpolobia lutea Leaf - Lucky Lebgosi Nwidu, Paul Alozie Nwafor, Wagner Vilegas (Journal of Applied Pharmaceutical Science)
Carpolobia lutea leaves (CLL) (Polygalaceae) were earlier screened and the antiulcer ethnomedicinal claim established. This article seeks to quantitatively isolate, elucidate the active compounds from most active CLL fraction. Fractionation was by semi-preparative HPLC; the active fraction was subjected to radical scavenging assays (RSA) and quantification of the total phenolic content (TPC) were also executed. Results: Ethyl acetate fraction (EAF) was observed to be the most pharmacologically active antiulcer fraction when screened using acute ulcer models induced in rodents. The EAF demonstrated significant (p
Keywords: Carpolobia lutea,Polygalaceae, cinnamoyl-,coumaroyl- 1-deoxyglucoside, ulcerogenic.